Spatial and temporal distribution of bacterial communities and heavy metals (CR, CD AND PB) composition in sediments along Pahang river, Malaysia - Mohd Amin, Mohd Huzaimi; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman; Nordin, Noor Faizul Hadry (Penerbit Universiti Teknologi Malaysia Press, 2015)
Bacterial communities show complex and sensitive response towards the environmental stimulation. Pahang River is one of the important inland aquatic biodiversity resources that provide food and excellent habitat for many organisms including microorganisms. Higher bacterial diversity is assumed to increase ecosystem capacity to resist and recover from perturbation. Hence, it is important to assess the impacts of heavy metals composition towards distribution of bacteria in sediments along Pahang River. A study on heavy metals composition such as chromium, cadmium and lead was carried out along the Pahang River using Teflon Bomb digestion processes and were analyzed using ICP-MS. Overall 19 sampling areas along Pahang River with frequency of 20-30 km for each site were chosen as our sampling stations. Sampling was conducted during pre and post of North-East monsoon season. The average dry weight concentration for chromium (Cr) was found between 3.250 and 21.950 μg/g, cadmium (Cd) ranged from 0.019 to 0.403 μg/g and lead (Pb) 8.024 to 20.660 μg/g. The bacterial community in sediments along Pahang River was determined using culture-based method. The bacterial colony-forming unit (CFU) range was found between 1013.33 CFU/g and 28826.67 CFU/g. This study demonstrated that the concentration of heavy metals and bacterial colony number different at each station during pre and post-monsoon. Apart from that, the heavy metals composition can influence the changes of bacterial colony number. However this changes also influence by other factors such as physicochemical parameters, sediments size, nutrient contents in the river and also sediments and water run-off. The condition of Pahang River is still conducive and activities that causing pollution should be stopped.